A neurophenomenology of awe and wonder : towards a non-reductionist cognitive science /: towards a non-reductionist cognitive science. (2015) - Gallagher, Shaun, 1948-; Janz, Bruce B, 1960-; Reinerman, Lauren; Bockelman, Patricia; Trempler, Jörg
No abstract available